Editorial: A New Chapter for IJIMAI - Rubén González-Crespo (International Journal of Interactive Multimedia and Artificial Intelligence)
The history of IJIMAI is a story of commitment, inclusion, and accessibility within the academic world. Since its founding, the journal has aimed to provide an open, free, and high-quality space for researchers and professionals in the fields of artificial intelligence and interactive technologies. The decision to offer open access to all was a clear commitment to democratizing knowledge and making scientific advances available to the entire community without financial barriers or access restrictions. Furthermore, IJIMAI has been developed, to date, on an open-source platform, underscoring our commitment to the values of transparency, accessibility, and global collaboration. Throughout these volumes, IJIMAI has maintained a rigorous approach and an interdisciplinary vision, allowing us to address relevant topics from artificial intelligence and machine learning to interactive multimedia and complex systems. Each issue has been the product of a shared effort among authors, reviewers, and the editorial team, all working tirelessly to provide high-quality research and to promote scientific advancement in key areas.